Open-transistor Fault Detection and Diagnosis Based on Current Trajectory in a Two-level Voltage Source Inverter. (2016) - Raj, Nithin; Mathew, Jose; Jagadanand, G.; George, Saly
Abstract: Even though technological developments in the area of control of voltage source inverter (VSI) have reached a relatively matured state, advances in improving the reliability of VSI is still a developing area. In order to improve safety as well as reliable operation, an effective fault detection and diagnosis method has to be integrated along with the control of inverter-fed systems. In this paper, implementation of open-transistor fault detection and diagnosis in VSI is presented. The current trajectory of phase currents is employed to detect the fault condition and identify the faulty switch. Implementation of this method in a three-phase two-level VSI with the aid of data acquisition card and LabVIEW software is presented with the experimental result.